2005
DOI: 10.1089/dia.2005.7.253
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Approach to Continuous Glucose Analysis Utilizing Glycemic Variation

Abstract: We advocate an approach to the analysis of CGMS data based upon a hierarchy of relevant clinical questions alluding to the representative nature of the data, the amount of time spent in glycemic excursions, and the degree of glycemic variation. Integrated use of these algorithms distinguishes between various patterns of glycemic control in those with and without diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
256
2
4

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 314 publications
(266 citation statements)
references
References 25 publications
4
256
2
4
Order By: Relevance
“…So, to account for the influence of the method chosen, we calculated various different markers for glucose variability. The mean MODD and CONGA-1 for the 25 patients in our study appeared to be similar to values reported for ten patients with type 1 diabetes in an earlier study [19] (MODD, 4.0 mmol/l vs 4.3 mmol/l and CONGA-1, 2.5 mmol/l, in that and our studies). The mean MAGE in our study was higher than previously reported for 21 patients with type 2 diabetes (8.3 vs 4.2 mmol/l) [11], confirming that glucose variability in patients with type 1 diabetes is higher than in those with type 2 diabetes.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…So, to account for the influence of the method chosen, we calculated various different markers for glucose variability. The mean MODD and CONGA-1 for the 25 patients in our study appeared to be similar to values reported for ten patients with type 1 diabetes in an earlier study [19] (MODD, 4.0 mmol/l vs 4.3 mmol/l and CONGA-1, 2.5 mmol/l, in that and our studies). The mean MAGE in our study was higher than previously reported for 21 patients with type 2 diabetes (8.3 vs 4.2 mmol/l) [11], confirming that glucose variability in patients with type 1 diabetes is higher than in those with type 2 diabetes.…”
Section: Discussionsupporting
confidence: 91%
“…Inter-day glycaemic variability The day-to-day variation of the glucose pattern was calculated with the mean of the daily differences (MODD), which is defined as the mean of the absolute differences between glucose values on day 2 and the corresponding values on day 1, at the same time [19,20].…”
Section: Assessment Of Glycaemic Variabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…The HBGI and LBGI, as described by Clarke and Kovatchev [20], are summary indices reflecting the risk for hyperglycemia and hypoglycemia, respectively. Glycemic variability, which reflects acute glucose fluctuations, was assessed by the standard deviation of the average 24 h glucose concentration (SD) and by continuous overlapping net glycemic action (CONGA) as described by McDonnell et al [21]. With this method, the difference between each glucose reading and the glucose reading n hours previously is calculated.…”
Section: Continuous Glucose Monitoringmentioning
confidence: 99%
“…2,3 Currently, the statistics and metrics used to reflect glucose dynamics include, but are not limited to, the overall SD from a mean glucose value, percentage of values within, above, or below specified thresholds, area under the curve, mean amplitude of glycemic excursion (MAGE), 4 mean of daily differences (MODD), 5 and continuous overall net glycemic action (CONGA) (for the indicated n hours). 6 Additional metrics include the M-value, 7 average daily risk range, 8 Glycemic Risk Assessment Diabetes Equation scores, 9 and J-index. 10 Inconsistencies, however, can arise from the miscalculation, misinterpretation, and misuse of these metrics in disparate data types and applications.…”
Section: Introductionmentioning
confidence: 99%